Mode-of-action and human relevance framework analysis for rat Leydig cell tumors associated with sulfoxaflor. (May 2014) - Rasoulpour, Reza J.; Terry, Claire; LeBaron, Matthew J.; Stebbins, Kenneth; Ellis-Hutchings, Robert G.; Billington, Richard
Abstract Sulfoxaflor, a molecule that targets sap-feeding insects, was assessed for carcinogenic potential in groups of 50 Fischer rats fed with diets containing 0, 25, 100, 500 (males), or 750 (females) ppm sulfoxaflor for 2 years according to OECD 453. Sulfoxaflor did not alter the number of rats with Leydig cell tumors (LCTs: 88% of controls and 90–92% in treated groups). The size of LCT was increased at 100 and 500 ppm. The spontaneous incidence of LCT in Fischer rat is 75–100% compared with less than 0.01% in humans. These fundamental interspecies differences in spontaneous incidence of LCT are the result of quantitative and qualitative differences in Leydig cell response to hormonal stimuli. There are nine known modes of actions (MoA) for LCT induction. Analysis sulfoxaflor data suggested a hormone-based dopamine enhancement MoA causing the LCT effect through: 1) increased neuronal dopamine release via specific dopaminergic neuron-based nicotinic acetylcholine receptor (nAChR) agonism, leading to 2) decreased serum prolactin (Prl) levels, 3) downregulation of luteinizing hormone receptor (LHR) gene expression in Leydig cells, 4) transient decreases in serum testosterone, 5) increased serum LH levels, and 6) promotion of LCTs. The analysis suggested that sulfoxaflor promoted LCTs through a subtle stimulation of dopamine release. The MoA for LCT promotion in the carcinogenicity study is considered to have no relevance to humans due to qualitative and quantitative differences between rat and human Leydig cells. Therefore, the Fischer 344 rat LCT promotion associated with lifetime administration of high-dose levels of sulfoxaflor would not pose a cancer hazard to humans.